Oportunidades para el desarrollo y comercialización del software Desqubra en riesgo de lavado de activos y financiación del terrorismo, para empresas del sector Inmobiliario y turismo en México (2021)
The importance of companies as a contribution to the economic growth of any country has always been fundamental, so it is necessary to recognize that they are job creators and promoters of investment and development; But for several decades, certain companies have been affected by the incursion of illicit money by drug trafficking and criminal groups. As a result of this worrying situation, governments and companies in the real sector decide that they must establish a control for Money Laundering and Terrorism Financing (LAFT) together with other types of organizations such as the Financial Information and Analysis Unit (UIAF), and the countries that intervene the most in these practices end up being Colombia and Mexico in Latin America.